Development of Interactive Multimedia-Based Learning Media for Periodic Maintenance Competencies to Improve Learning Outcomes of Ma'arif Vocational School Students - Ahmad Tarmidi; Aci Primartadi; Dwi Jatmoko; Ahmad Masrur (Jurnal Locus Penelitian dan Pengabdian, 2026)
This research aims to produce interactive learning media for the periodic maintenance competency at SMK Ma'arif 6 Ayah, assess the feasibility of interactive multimedia learning media for the periodic maintenance competency, and measure the improvement in student learning outcomes following the use of interactive multimedia learning media for the periodic maintenance competency. The development of the interactive learning media employed a Research and Development (R&D) research method. Small-scale field trials were conducted with 12 students, and large-scale field trials were conducted with 32 Grade XII students of the Light Vehicle Engineering study program at SMK Ma'arif 6 Ayah. The trial results fell within the very feasible category, with the following details: material expert evaluation yielded a score of 88.25% (very feasible); media expert evaluation yielded a score of 87.75% (very feasible); small-scale student trials yielded a score of 89% (very feasible); and large-scale student trials yielded a score of 89.75% (very feasible). Based on these results, it can be concluded that the interactive multimedia-based learning media for the periodic maintenance competency is very feasible for use as a learning medium and is effective in improving student learning outcomes. This medium can therefore serve as an alternative solution in automotive practical learning, particularly at SMK Ma'arif 6 Ayah, and may be adapted for other subjects requiring practice-based procedural understanding.